A alienação do indivíduo em Max Horkheimer - Tourinho, Leila Silvia Latuf Seixas (2011)
This paper seeks to analyze the phenomena of the individual‟s alienation in the works of Max Horkheimer, taking as a base the phenomena of alienation described by Karl Marx in the Economic Philosophical Manuscripts. The objective is to show that the production relations described by Marx are rebound on other relationships that permeate the individual‟s social life. This hypothesis is examined in the light of Horkheimer‟s thoughts, and sustained by the social and historical transformations in which the individual found themselves inserted. First, some essays from the thirties are analyzed, they retract social contradictions by pointing such occurrences, but they also portray the hope that effective knowledge could promote the social transformation. Later, reflecting about the barbarism that occurred in the forties and about the increasingly strengthened state, Horkheimer takes a more pessimistic look in his new essays, translating into reflections the rationalization of the dominant thought and the non differentiation of the individual in the modern world. In this sense, the question that drives the development of this work is to show the philosophical statute which the concept of individual and its subsequent alienation occupy in the philosopher‟s thoughts, as well as show the contradiction of reason, more and more confident, empowered and serving the individual interests and at the same time, making it weak in the task of serving humanity. Emphasize that the reason is eclipsed and not destroyed credit to the author the trust he places in the individual to conduct a dignified human life